A Situation of the Crimeans Diocese of the Orthodox Church of Ukraine in Russian Occupied Crimea (2014-2022) - Ivanets, Andrii (Occasional papers on religion in Eastern Europe, 2022)
The article is devoted to the situation regarding the Crimean Diocese of the Orthodox Church of Ukraine after the annexation of Crimea by the Russian Federation. It should be noted that Orthodoxy and Islam are the most common religions on the peninsula. The Crimean Diocese of the Orthodox Church of Ukraine is the largest and most prominent among the Crimean religious organizations. The authors highlight Russia's consistent discriminatory policy toward the Ukrainian Orthodox Church-Kyiv Patriarchate/the Orthodox Church of Ukraine on the temporarily occupied peninsula, which is aimed at their gradual but rigorous expulsion from Crimea. The methods of its implementation are elucidated. Currently, the number of parishes has decreased by more than six times, and the number of clergies has reduced by almost six times under pressure from the occupation authorities. Practically, the diocese has been placed on the brink of existence. The Russian large-scale invasion of Ukraine in February 2022 worsened the crisis of the Orthodox Church of Ukraine in Crimea. An analysis of the conditions of its activities in 2014-2022 leads to the conclusion that there is a persistent negative trend toward the deterioration of its situation. The policy of the occupying state is not simply aimed at violating the rights of believers of this religious organization, but at gradually creating conditions for the termination of its activities. Russia's discrimination against the Crimean Diocese of the PCU is not only a gross violation of the rights of believers, but also pressure on the community of ethnic Ukrainians in Crimea, whom the occupation authorities have turned into one of the two most discriminated ethnic communities in the region. This religious organization is an important center for the maintenance of Ukrainian identity for Crimean Ukrainians in the conditions of Russia's destruction of Ukrainian socio-political and cultural-educational institutions in Crimea. The rights of Crimean believers of the Orthodox Church of Ukraine can be fully protected only after the liberation of Crimea and the restoration of Ukraine's territorial integrity. Until then, the Ukrainian state and civil society, international organizations, and civilized countries should use methods that at least partially relieve pressure on this religious organization.